Structural evolution of ZTA composites during synthesis and processing. Issue 4 (April 2015) - Exare, C.; Kiat, J.-M.; Guiblin, N.; Porcher, F.; Petricek, V.
Abstract We have studied the structural properties of industrial Zirconia Toughened Alumina (ZTA) composites for different compositions of zirconia and yttria at the main stages of the process. Influences on phases stability, lattice parameters, homogeneous and non-homogeneous strains, particles and crystallites sizes, have been considered and discussed. The structural states are explained from a very delicate balance of three competing effects: yttria-doping, strain and size effect. The first and third one have been shown to stabilize the tetragonal phase relatively to the monoclinic phase, and to destabilize the tetragonal phase relatively to the cubic phase whereas the second one is doing the opposite. In addition to this competition, the most prominent local effects have also being considered to fully understand the microscopic situation: i.e. the micro-strains and the inhomogeneous distribution of yttria which both increases the metastable coexistence of phase. At high yttria content a core–shell structure of the grains is evidenced.